2009
DOI: 10.1248/bpb.32.1289
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Isoflavone Pratensein as a Novel Transcriptional Up-Regulator of Scavenger Receptor Class B Type I in HepG2 Cells

Abstract: Scavenger receptor class B type I (SR-BI), as well as its human homologue CLA-1, plays an important role in reverse cholesterol transport (RCT) as high density lipoprotein (HDL) receptor. Using a previously developed cell-based screening model for CLA-1 up-regulators, pratensein, was shown to present activity in elevating CLA-1 transcriptional level. In this study, three other isoflavones including formononetin, genistein and daidzein were also shown to up-regulate CLA-1 transcriptional activity in the cell-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Hydrophilic constituents of Danshen, including SAB and danshensu, were shown to inhibit CD36-OxLDL binding and consequently inhibit foam cell formation . Moreover, daidzein, a hydrophilic constituent of Gegen, was also found to play a role in inhibition of foam cell formation indirectly via up-regulation of scavenger receptor class B type I (SR-BI), which can facilitate cholesterol efflux from macrophages (Yang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Hydrophilic constituents of Danshen, including SAB and danshensu, were shown to inhibit CD36-OxLDL binding and consequently inhibit foam cell formation . Moreover, daidzein, a hydrophilic constituent of Gegen, was also found to play a role in inhibition of foam cell formation indirectly via up-regulation of scavenger receptor class B type I (SR-BI), which can facilitate cholesterol efflux from macrophages (Yang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…To date, the techniques of new drug high throughput screening consist of protein chip, polarized fluorescence, high content screening, model organisms, and cell models [22–27] . The cell models can simulate a variety of signalling pathways and imitate the in‐vivo effects of drugs on human or animals, and so they are successfully used in drug screening studies and are also suitable for high‐throughput screening [28] .…”
Section: Discussionmentioning
confidence: 99%
“…To date, the techniques of new drug high throughput screening consist of protein chip, polarized fluorescence, high content screening, model organisms, and cell models. [22][23][24][25][26][27] The cell models can simulate a variety of signalling pathways and imitate the in-vivo effects of drugs on human or animals, and so they are successfully used in drug screening studies and are also suitable for high-throughput screening. [28] Our previous study demonstrated that HEK293T cells expressed very lower hPPARg in itself, and phPPARg-IRES2-EGFP expression vector carrying human hPPARg gene could be efficiently transfected and expressed in HEK293T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Pratensein and several other isoflavones were identified as active compounds to upregulate SR-BI expression in vitro [96]. After screening from 6000 microbial secondary metabolite crude extracts, trichostatin A (TSA), a well-known histone deacetylase inhibitor was identified to effectively increase SR-BI transcription.…”
Section: Sr-bi Modulatorsmentioning
confidence: 99%
“…These results warrant further pharmacological target identification and validation and new drug discovery targeting miRNAs. ApoA-I Cell-based protein assay Upregulation of ApoA-I expression [46] Transcriptional reporter assay Increasing ApoA-I transcription [52,53,56,57] ABCA1 Transcriptional reporter assay Increasing ABCA1 transcription [58][59][60][61] Ligand-binding assay Modulating ABCA1 binding activity [64,65] Functional assay Increasing ABCA1-mediated cholesterol efflux [63] SR-BI Transcriptional reporter assay Increasing SR-BI transcription [95][96][97] Functional assay Modulating selective cellular uptake of lipid from HDL [100,101] LXR Ligand-binding assay Activating the ligand-binding domain of LXR In fact, HDL has not yet been thoroughly exploited for therapy owing to the structural and functional complexity of HDL particles. Recent studies have indicated that myeloperoxidase oxidized ApoA-I in human atheroma and a dysfunctional form of ApoA-I/HDL was generated [137].…”
Section: Expert Opinionmentioning
confidence: 99%